Massive Crimes, Individual Tragedies. The Unbearable Truths of Transitional Justice - Suárez, Andrés Fernando (Sociedad y Economía, 2024)
This article explores the relationship between the acknowledgment of mass crimes and the elucidation of individual tragedies within the judicial contexts of transitional justice. It reviews and analyzes the narratives of victims and perpetrators across various judicial scenarios within the transitional justice models of the Justice and Peace Law and the Special Jurisdiction for Peace in Colombia. The findings reveal a discrepancy between the truths presented by those most accountable and the truths anticipated by the victims. Both parties perceive these truths as highly contentious and unbearable, underpinned by suspicion and mutual distrust. Many of these unbearable truths stem from oblivion and ignorance, deindividualization, organizational compartmentalization, arbitrariness beyond complicity, and disregard for civilians and their recognition as victims. These realities are deeply intertwined with the dynamics of the armed conflict.